Empowerment of Women "Sampah Berkah" Based on Literacy and Inclusion Methods - S. Purnamasari; Purnama Rozak; Kurniaty; Umi Hani; A. Hadi; Yunisa F (Indonesian Journal of Advanced Social Works, 2023)
The real impacts of globalization, the post-covid-19 pandemic era and even the economic recession era in 2023 include sharp disparities in all fields which have given rise to their own phenomena in society. Community empowerment, especially women's empowerment, is the key to the success of social change programs to change the quality of life and public health for the better. As is the government's commitment to the Millennium Development Goals (MDGs), which include trying to empower women through education, increasing their role in society, the economy, and so on. The problems in this service activity are the lack of knowledge of women focused on housewives about the economic value of waste, MSMEs, and financial institutions both sharia and conventional as investment media, loans for daily needs/business capital as well as the lack of training and mentoring for women. focused on housewives in understanding how/procedures to make transactions with service providers or financial institutions. This community service activity is carried out in the form of active participatory empowerment, coaching and focus group discussions (FGD) as well as group counseling using literacy and inclusion methods, which includes coaching (educating, training and mentoring) through activeness and consultation between partners and the service team. in discussion. As a result, partners can have good knowledge regarding the economic value of waste, UMKM, and financial institutions, both sharia and conventional.